David William Smith: Surveyor as State-Builder - Alexander, Christopher (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
David William Smith, the first Surveyor General of Upper Canada, the second largest landowner ever in Pickering Township, and, at one time, the owner of most of the land that is now Ajax, was Lieutenant Governor John Graves Simcoe’s most consistent administrator and the principal architect and implementer of the province’s new and complex land-granting system. However, his many accomplishments have been largely overlooked. This article seeks to return Smith to his rightful place as a key shaper in early Upper Canada’s fortunes.